Peningkatan Hasil Belajar Pada Pembelajaran Tematik Terpadu dengan Model Problem Based Learning Kelas IV Sekolah Dasar - Banovi, Fadillah Annisa; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The research aims to describe the learning results improved in integrated thematic learning with PBL model in class IV SDN 18 Air Tawar Selatan Kota Padang. This type of research is classroom action research using approach qualitative and quantitative. The techniques used are observation, test, and nontest. Observational research results RPP cycle I with 82% percentage increase in cycle II becomes 97%. Aspects of teacher cycle I with 82% percentage increase in cycle II becomes 96%. Aspects of student cycle I with 82% percentage increase in cycle II become 96%. Aspects of the knowledge cycle I with an average 70 increase in cycle II with average 92. Aspects of skills cycle I with average 73 increase in cycle II with average 92. This proves that the PBL model can improve student  learning outcomes.